The Effect of the Ratio of Mocaf and Soybean Flour with Addition of Glucomannan on Physical, Chemical and Sensory Properties of Gluten-Free Wet Noodles - Violalita , Fidela; Yanti, Henny Fitri; Evawati, Evawati; Roza, Irwan; Ermiati, Ermiati; Fahmy, Khandra; Yuswilara, Yuswilara; Saputra, Afdal (Green Engineering Society, 2024)
The primary ingredient used to make noodles is typically wheat flour. However, not everyone can consume wheat flour. Gluten-free noodles are suitable for individuals who avoid gluten, particularly those with celiac disease and autism. Some ingredients used to make gluten-free noodles include mocaf, soybeans, and glucomannan. This study aims to determine the characteristics and optimal formulation of gluten-free wet noodles made from mocaf, soybean, and glucomannan flour. This research method uses a Completely Randomized Design (CRD) factorial with two factors and three replications. The first factor is the ratio of mocaf flour to soybean flour, consisting of 3 levels: 80:20 (A1), 75:25 (A2), and 70:30 (A3). Another factor is the addition of glucomannan flour, consisting of 3 levels: 2% (B1), 5% (B2), and 8% (B3). The analysis performed on these wet noodles includes physical, chemical, and sensory evaluations. The comes about of the study appeared that noodles with the ratio of mocaf flour to soybean flour 75:25 and the addition of 2% glucomannan flour (A2B1) is the best treatment based on the highest elasticity with elasticity 73.3%, water absorption, 89.3%, swelling index 271%, cooking loss 8.78%, water content 36.8%, protein 6.44%, ash 1.89%, fat 0.74%, carbohydrate 50.4%, sensory test results appearance 3.76 (somewhat like), color 3.72 (somewhat like), aroma 3.2 (neutral), texture 3.36 (neutral), and taste 3.36.